Handbook of crack opening data : a compendium of equations, graphs, computer software, and references for opening profiles of cracks in loaded components and structures - Gray, T. G. F. (Abington Pub., 1992)
Written mainly for specialists in non-destructive examination and fracture mechanics, this book provides means to estimate the opening profiles of cracks in loaded structures. Equations, non-dimensional graph plots, computer software, background information and references are given which permit the calculation of the separation distances of crack faces as a function of crack size, applied loading etc. Sixteen different cases are covered by this Handbook. An Abington Publishing Special Report.